Dietary diversity and determinants of young adults in central China: A cross-sectional study from 2015 to 2020 - Zhou, Yi; Wang, Jiangang; Duan, Yinglong; Luo, Xiaofei; Wan, Ziyu; Luo, Yating; Li, Ying; Wang, Yaqin; Xie, Jianfei (Frontiers in Nutrition, 2022)
Background: Early adulthood is a vulnerable period for improved nutrition at all phases of the life cycle. However, there is limited research on diversity information in young adults from middle-income countries undergoing an apparent nutritional transition. The purpose of this study was to explore dietary diversity and determinants among young adults aged 18-35 years in central China. Methods: From January 2015 to December 2020, a cross-sectional survey of 49,021 young adults in a health management center of central China was conducted through report and phone-assisted self-report for information. The outcome variable was the Dietary Diversity Score. Independent variables included age, sex, race, material status, education, BMI, taste preference, regular meals, midnight snacks, sugared beverage/coffee consumption and smoking/drinking status. Multivariate logistic regression was performed. Results: Of 49,021 young adults, 38,374 (78.3%) reported insufficient dietary diversity, and 422 (0.9%) reported sufficient dietary diversity. Light taste preference (adjusted odds ratio [aOR]=2.325; 95% CI: 1.779, 3.039) and those who had meals regularly (aOR=1.241; 95% CI: 1.018, 1.513) and consumed coffee (aOR=2.765; 95% CI: 2.257, 3.387) were more likely to be associated with sufficient dietary diversity. Midnight snacks (aOR = 0.728; 95% CI: 0.588, 0.901) and sugary beverages (aOR=0.666; 95% CI: 0.535, 0.829) were less likely to be associated with sufficient dietary diversity. Higher BMI (aOR=1.092; 95% CI: 1.061, 1.125) was associated with higher odds of sufficient dietary diversity. Additionally, participants who were 18-30 years old, with master or above degree and away from cigarette/alcohol were more likely to report better dietary diversity. Conclusion: Our results painted a less than ideal nutritional condition affecting young adults. High-fat/sugar/salt dietary practices can lead to low dietary diversity, while high dietary diversity might have adverse BMI outcomes in youth. This study highlighted the importance of increasing the diversity of healthy and selective food items before wide recommendation for dietary diversity.